Ответы и объяснения

2013-05-03T14:32:02+04:00

4 х ² + 6 х - 2 = (х - 1)²

4 х ² + 6 х - 2 = х ² - 2 х + 1

4 х ² + 6 х - 2 - х² + 2 х - 1 = 0

3 х² + 8 х - 3 = 0

D = 64 + 4 * 3*3 = 64 + 36 = 100

 

х 1 = - 8 + 10   =         2

          ------------      --------- = 1/3

                 6                 6       

 

х 2 = - 8 - 10

         ----------  = - 3

                6

2013-05-03T14:37:51+04:00

4х^2+6х-2=(х-1)^2

4x^2+6x-2=x^2-2x+1

4x^2+6x-2-x^2+2x-1=0

3x^2+8x-3=0

D=(8)^2-4*3*(-3)=64+36=100

x1=-8+10/6=1/3

x2=-8-10/6=-3

(1/3.-3)